Online mediation due to the quarantine caused by COVID-19 Pandemic - Неугодніков, Андрій Олександрович; Неугодніков, А. О.; Неугодников, Андрей Александрович; Neuhodnikov, Andrii O.; Neugоdnikov, Andrii; Донцов, Денис Юрійович; Донцов, Д. Ю.; Донцов, Денис Юрьевич; Dontsov, Denys Yu.; Бігняк, Олександр Валентинович; Бігняк, О. В.; Бигняк, Александр Валентинович; et al. (University of Zulia, 2021)
The institute of mediation is becoming increasingly popular. This is due to several factors, including the possibility to save on attorneys' fees and court costs. Mediation also helps to save a lot of time and find a solution to the conflict that would satisfy both parties as quickly as possible. During the pandemic, the institution of mediation, like many other spheres of public life, moved online. The mediation process itself involves individuals who use online communication or even artificial intelligence, such as chatbots. Thus, in connection with the transition of mediation to the online plane, there is a need for legal support for the use of innovative technologies in the field of mediation. Thus, the article is relevant and timely in terms of quarantine restrictions. The object of research is public relations in the field of online mediation. The authors of the article used general and special research methods. The authors of the article concluded that online mediation is a useful institution, but the implementation of appropriate procedures must take care to protect private information, as there is no full control over the situation outside the camera of a computer, tablet, phone, or other device with access on the Internet.

Інститут медіації стає все більш популярним. Це пов’язано з кількома факторами, зокрема можливістю заощадити на гонорарах адвокатів та судових витратах. Медіація також допомагає заощадити багато часу та якомога швидше знайти рішення конфлікту, яке б задовольнило обидві сторони. Під час пандемії інститут медіації, як і багато інших сфер суспільного життя, перемістився в Інтернет. Сам процес посередництва включає людей, які використовують онлайн-спілкування або навіть штучний інтелект, наприклад чат-ботів. Таким чином, у зв’язку з переходом медіації в онлайн-площину виникає потреба в правовому забезпеченні використання інноваційних технологій у сфері медіації. Таким чином, стаття є актуальною та своєчасною з точки зору карантинних обмежень. Об’єкт дослідження – зв’язки з громадськістю у сфері онлайн-посередництва. Автори статті використали загальні та спеціальні методи дослідження. Автори статті дійшли висновку, що онлайн-посередництво є корисним інститутом, але виконання відповідних процедур має подбати про захист приватної інформації, оскільки немає повного контролю над ситуацією поза камерою комп’ютера, планшета, телефону чи іншого пристрою з виходом в Інтернет.
Dontsov D., Neugodnikov A., Bignyak O., Kharytonova O., Panova L. Online mediation due to the quarantine caused by COVID-19 Pandemic / D. Dontsov, A. Neugodnikov, O. Bignyak, O. Kharytonova, L. Panova // Cuestiones Políticas. - Vol. 39. - Issue 68. - University of Zulia, 2021. - Р. 914-926.
Keywords: alternative dispute resolution; online mediation; peaceful dispute resolution procedure; information technology; mediator; альтернативне вирішення спорів; онлайн-медіація; процедура мирного вирішення спорів; інформаційні технології; медіатор; Research Subject Categories::LAW/JURISPRUDENCE